Linear and nonlinear optical absorption coefficients in GaAs/Ga1−xAlxAs concentric double quantum rings : Effects of hydrostatic pressure and aluminum concentration (2013)
ABSTRACT: The linear and nonlinear intra-band optical absorption coefficients in GaAs/Ga1−xAlxAs two-dimensional concentric double quantum rings are investigated. Taking into account the combined effects of hydrostatic pressure and aluminum concentration the energies of the ground and the first excited state have been found using the effective mass approximation and the transfer matrix formalism. The energies of these states and the corresponding threshold energy of the intra-band optical transitions are examined as a function of hydrostatic pressure and aluminum concentration for different sizes of the structure. We also investigated the dependencies of the linear, nonlinear, and total optical absorption coefficients as functions of the incident photon energy for different values of hydrostatic pressure, aluminum concentration, sizes of the structure, and incident optical intensity. Its is found that the effects of the hydrostatic pressure and the aluminum concentration lead to a shifting of the resonant peaks of the intra-band optical spectrum.